Bone response to loading in mice with targeted disruption of the cartilage oligomeric matrix protein gene - Sengul, A; Mohan, S; Kesavan, C (Physiological research, 2012)
Exercise induced bone response although established, little is known about the molecular components that mediate bone response to mechanical loading (ML). In our recent QTL study, we identified one such possible molecular component responding to ML: cartilage oligomeric matrix protein (COMP). To address the COMP role in mediating ML effects on bone formation, COMP expression was evaluated as a function of duration and age in response to ML in female B6 mice. A 9N load was applied using a four-point bending device at 2Hz frequency for 36 cycles, once per day for 2-, 4- and 12-days on the right tibia. The left tibia was used as an internal control. Loading caused an increase in COMP expression by 1.3-, 2- and 4-fold respectively after 2-, 4- and 12-days of loading. This increase was also seen in 16 and 36-week old mice. Based on these findings, we next used COMP knockout (KO) mice to evaluate the cause and effect relationship. Quantitative analysis revealed 2 weeks of ML induced changes in vBMD and bone size in the KO mice (5.9 % and 21 % vs. unloaded bones) was not significantly different from control mice (7 % and 24 % vs. unloaded bones). Our results imply that COMP is not a key upstream mediator of the anabolic effects of ML on the skeleton.
Keywords: myši; Mice, Knockout; myši knockoutované; Stress, Mechanical; Weight-Bearing; Glycoproteins; Extracellular Matrix Proteins; Mice; Osteogenesis; Animals; zatížení muskuloskeletálního systému; glykoproteiny; zvířata; osteogeneze; mechanický stres; kosti a kostní tkáň; Bone and Bones; ženské pohlaví; extracelulární matrix - proteiny; Quantitative Trait Loci; Female; lokus kvantitativního znaku